How Loud Can you go? Physical and Physiological Constraints to Producing High Sound Pressures in Animal Vocalizations - Jakobsen, Lasse; Christensen-Dalsgaard, Jakob; Juhl, Peter Møller; Elemans, Coen P. H. (Frontiers in Ecology and Evolution, 2021)
Sound is vital for communication and navigation across the animal kingdom and sound communication is unrivaled in accuracy and information richness over long distances both in air and water. The source level (SL) of the sound is a key factor in determining the range at which animals can communicate and the range at which echolocators can operate their biosonar. Here we compile, standardize and compare measurements of the loudest animals both in air and water. In air we find a remarkable similarity in the highest SLs produced across the different taxa. Within all taxa we find species that produce sound above 100 dBpeak re 20 µPa at 1 meter, and a few bird and mammal species have SLs as high as 125 dBpeak re 20 µPa at 1 meter. We next used pulsating sphere and piston models to estimate the maximum sound pressures generated in the radiated sound field. These data suggest that the loudest species within all taxa converge upon maximum pressures of 140-150 dBpeak re 20 µPa in air. In water, the toothed whales produce by far the loudest SLs up to 240 dBpeak re 1 µPa at 1 meter. We discuss possible physical limitations to the production, radiation and propagation of high sound pressures. Furthermore, we discuss physiological limitations to the wide variety of sound generating mechanisms that have evolved in air and water of which many are still not well-understood or even unknown. We propose that in air, non-linear sound propagation forms a limit to producing louder sounds. While nonlinear sound propagation may play a role in water as well, both sperm whale and pistol shrimp reach another physical limit of sound production, the cavitation limit in water. Taken together, our data suggests that both in air and water, animals evolved that produce sound so loud that they are pushing against physical rather than physiological limits of sound production, radiation and propagation.